2023
DOI: 10.3390/insects14020106
|View full text |Cite
|
Sign up to set email alerts
|

Fermented or Floral? Developing a Generalized Food Bait Lure to Monitor Cutworm and Armyworm Moths (Lepidoptera: Noctuidae) in Field Crops

Abstract: Cutworms and armyworms (Lepidoptera: Noctuidae) are a pest complex in North America that cause sporadic damage in field crops on the Canadian Prairies; however, no methods have been developed to reliably monitor population densities. Food-based semiochemicals attract both sexes of adult moths and could be used to monitor multiple species with a single lure in a single trap. Here, we focus on enhancing the attractiveness of acetic acid and 3-methyl-1-butanol (AAMB) lures to redbacked cutworm (Euxoa ochrogaster)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Finally, there were 2 compounds, 4-oxododecanedioic acid dominating in the digesta of experimental chickens and phenylacetaldehyde dominating in control chickens, both having a relationship to insects. Phenylacetaldehyde is common in flowers where it acts as an insect attractant ( Batallas and Evenden, 2023 ). Microbiota composition affecting phenylacetaldehyde levels in the digesta and fecal material can therefore affect transmission of gut microbiota by insects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there were 2 compounds, 4-oxododecanedioic acid dominating in the digesta of experimental chickens and phenylacetaldehyde dominating in control chickens, both having a relationship to insects. Phenylacetaldehyde is common in flowers where it acts as an insect attractant ( Batallas and Evenden, 2023 ). Microbiota composition affecting phenylacetaldehyde levels in the digesta and fecal material can therefore affect transmission of gut microbiota by insects.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of host bean volatile increased attractiveness in 2015, supporting conclusions drawn by Evenden et al (2016) and St. Onge et al (2018); however, this trend was not observed in 2016. In addition to the semiochemical blend used in lures, lure type and dose can affect the number of insects captured in traps (Jansson et al 1993; Byers 2013; Luo et al 2020; Ebbenga et al 2022; Batallas and Evenden 2023). Surprisingly, pheromone dose (10 mg versus 21 mg) and lure type (septa versus microcentrifuge tube, respectively) had no effect on the abundance of S. lineatus captured in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pheromone-based monitoring programs require individual traps and specific lures for each species, making monitoring several pests costly and time time-consuming. Batallas and Evenden [9] explored the development of a foodbased semiochemical lure to monitor both sexes of the cutworm and armyworm pest complex with a single trap and lure and with a minimum impact on native pollinators. Field experiments were conducted in canola and wheat fields in the Canadian Prairies to evaluate the activity of the AAMB lure (mixture of acetic acid and 3-methyl-1-butanol).…”
mentioning
confidence: 99%